2021
DOI: 10.3390/ijms22084080
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology of Atherosclerosis and Related Diseases: Focus on Molecular Biology

Abstract: In this Special Issue of the International Journal of Molecular Sciences, we include insightful reviews and research papers on the subject “Immunopathology of Atherosclerosis and Related Diseases: Focus on Molecular Biology”.[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…A large number of studies have shown that the pathogenesis of AS includes hyperlipidemia, vascular endothelial dysfunction, inflammation and oxidative stress [ 4 , 5 , 6 ]. Besides, the increased immunogenicity of desialylated low-density lipoprotein (LDL) and mitochondrial mutations were also involved in the development of AS [ 7 , 8 ]. Among them, endothelial dysfunction and inflammation play pivotal roles in the initiation of AS.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that the pathogenesis of AS includes hyperlipidemia, vascular endothelial dysfunction, inflammation and oxidative stress [ 4 , 5 , 6 ]. Besides, the increased immunogenicity of desialylated low-density lipoprotein (LDL) and mitochondrial mutations were also involved in the development of AS [ 7 , 8 ]. Among them, endothelial dysfunction and inflammation play pivotal roles in the initiation of AS.…”
Section: Introductionmentioning
confidence: 99%
“…In normal cases, a tolerance develops, and the macrophage stops releasing cytokines. However, in the presence of mitochondrial mutations, tolerance formation may be impaired, which could lead to continuous secretion of inflammatory cytokines and chronic inflammation development [ 3 , 4 ].…”
Section: Figurementioning
confidence: 99%
“…One promising hypothesis combining different observations related to atherosclerosis pathology is that mutations of mitochondrial DNA could modulate the inflammatory response of macrophages to different pro-inflammatory stimuli, leading to chronic inflammation and further development of the disease [ 3 , 4 ]. As a part of the innate immune system, macrophages are capable of recognizing pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), and can trigger immune response.…”
mentioning
confidence: 99%
“…Accumulating evidence indicates that numerous miRNAs play a pivotal role in both atherosclerotic initiation and progression. miRNAs are highly conserved, single-stranded noncoding RNA molecules, exerting post-transcriptional effects on gene expression by promoting degradation of mRNA target and/or inhibiting mRNA translation [ 37 ]. Accordingly, they participate in positive as well as negative regulatory loops resulting in a hierarchical network.…”
Section: Alternative Hypotheses On Atherosclerotic Lesion Initiation and Progressionmentioning
confidence: 99%